Cultural Competence and Cultural Intelligence of Healthcare Professionals Providing Emergency Medical Services - Anna Majda (MDPI AG, 2021)
Background: There are more and more foreigners in Poland who become clients of the Polish healthcare system. They use, among others, emergency medical services provided by healthcare professionals: doctors, nurses, and paramedics. Skillful care for culturally different patients requires cultural competencies and cultural intelligence to ensure good quality of care and cultural safety. The study aimed to measure and assess the cultural competencies and cultural intelligence of medical professionals working in hospital emergency departments (HEDs) and hospital emergency rooms (HERs) in Małopolska, a region in southern Poland. Methods: The following questionnaires were used in the study: the Cross-Cultural Competence Inventory (CCCI), the Cultural Intelligence Scale (CQS), and Questionnaire on Attitudes Towards Culturally Divergent People. In total, 709 medical professionals participated in the study, including 363 nurses, 223 paramedics, and 123 doctors. Results: Cultural intelligence—the overall score and the scores on the metacognitive, cognitive, motivational, and behavioral subscales were significantly higher among HED and HER doctors. Cultural competencies—the overall score and the score on the cultural adaptation subscale were also significantly higher among HED and HER doctors. The CCCI and CQS scores were influenced by selected variables: taking care of and close interactions with representatives of other cultural circles; staying outside Poland for more than a month. Doctors were the group of medical professionals that were most tolerant and most positive towards people from other cultures. Conclusions: The research results confirm the positive impact of contact of medical professionals with people from other cultures on their cultural competencies and cultural intelligence. They indicate the need for training in acquiring cultural competencies and developing cultural intelligence, especially among nurses. They demonstrate the need to raise awareness among HED and HER medical professionals about issues in intercultural care and to increase diversity efforts, especially among nurses.